2014
DOI: 10.1007/s13762-014-0713-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of various amendments on immobilization and phytoavailability of nickel and zinc in a contaminated floodplain soil

Abstract: The immobilization of toxic metals in soils using amendments is a cost-effective remediation technique for contaminated soils. Therefore, this study aimed to assess the efficiency of various amendments to immobilize nickel (Ni) and zinc (Zn) in soil and reduce their phytoavailability. A greenhouse pot experiment was established with a contaminated agricultural floodplain soil. The soil was treated with activated carbon (AC), bentonite (BE), biochar (BI), cement bypass kiln dust (CBD), chitosan (CH), coal fly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(16 citation statements)
references
References 53 publications
1
13
0
2
Order By: Relevance
“…These obtained findings also indicated that the application of calcite, RS, TSP, and ZE increased the reducible portion of Ni. It could be demonstrated that the incorporation of BI showed the formation of Fe-Mn oxides and bonds with the mineral phase of BI, which ultimately resulted in the formation of an insoluble stable complex form of metals (Shaheen et al, 2015). The oxidizable proportion of Ni was also significantly increased with the addition of 1% and 2% BI and recorded as 11.5% and 17%, respectively.…”
Section: Fractionation Of Nimentioning
confidence: 96%
See 2 more Smart Citations
“…These obtained findings also indicated that the application of calcite, RS, TSP, and ZE increased the reducible portion of Ni. It could be demonstrated that the incorporation of BI showed the formation of Fe-Mn oxides and bonds with the mineral phase of BI, which ultimately resulted in the formation of an insoluble stable complex form of metals (Shaheen et al, 2015). The oxidizable proportion of Ni was also significantly increased with the addition of 1% and 2% BI and recorded as 11.5% and 17%, respectively.…”
Section: Fractionation Of Nimentioning
confidence: 96%
“…Therefore, the immobilization of Ni contaminated soil has become an important task to reduce its mobility within the soil. For this purpose, various remediation techniques have been performed, including physiochemical approaches and phytoextraction (Shaheen et al, 2015;Bashir et al, 2018a). Recently, the use of several organic and inorganic passivators has attained a considerable attention for the remediation of Ni contaminated soils (Shaheen et al, 2015;Radziemska and Mazur, 2016;Khan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, improvement in soil CEC after the application of BN is responsible for the reduced phytoavailability of Pb. It has been reported that improvement in plant biomass and associated parameters are mainly due to the alleviation of Pb toxicity to the plants [7,26].…”
Section: Agronomic Photosynthetic and Biophysical Parameters Of Pea mentioning
confidence: 99%
“…2c&d). Because amendments with biochar and CFA primarily served to stabilize the weakly bound metals in soil via adsorption, complexation and precipitation due to increase of soil pH and additional sorption capacity Shaheen et al, 2014), this study showed that preceding 2-h EDDS washing enabled removal of bioavailable metals and thus significantly reduced the resultant DTPA-and SBET-extractable metals. Yet, there was little difference between the stabilization effectiveness of the three amendments (i.e., individual or combined applications of biochar produced at different temperatures and CFA), as indicated by the same letters and overlapping error bars of the same metals in Figs.…”
Section: Post-remediation Phytoavailability and Bioaccessibilitymentioning
confidence: 82%